PERLINDUNGAN PEREMPUAN PADA PENERAPAN SANKSI PIDANA HUKUM KELUARGA DALAM ADMINISTRATION OF MUSLIM LAW ACT 1966 SINGAPURA - Muftihatu Rahmah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
This article discusses the protection of women based on the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) in the application of criminal sanctions under the Administration of Muslim Law Act 1966 (AMLA) in Singapore. The research aims to analyze to what extent criminal sanctions in Islamic family law in Singapore have met the standards of women's protection set forth by CEDAW. This study employs a literature review approach using a gender justice perspective on women's protection as defined by CEDAW. The research findings indicate that the implementation of criminal sanctions under AMLA represents a significant step in safeguarding women. The criminal sanctions applied within AMLA provide legal assurance for women who experience violations within the context of family law, such as domestic violence, unlawful marriages, or the neglect of women's rights in divorce.